The Poverty Reality of Coastal and Agriculture: How Severe the Seaweed Farmers and Cocoa Smallholders Are? - Muhammad Arsyad; Andi Nuddin; Muhammad Yusri Zamhuri; Syarifuddin Yusuf (International Journal of Agriculture System, 2014)
This paper examines rural coastal-agricultural poverty by extracting and comparing poverty causal of seaweed farmer and cocoa smallholder households as a long standing issue in developing countries. The research employed (1) Foster-Greer-Torbecke (FGT) poverty indices for describing poverty situation, (2) Regression Analysis for extracting effects of explanatory variables on Poverty, and (3) Paired-Samples T Test to evaluate income differences. Some important findings are; (1) the degree of poverty between Seaweed Farmers and Cocoa Smallholders is significantly different, meaning they have a differentiation in income structure indicating the causes of poverty are different. FGT indices reveal that the depth of poverty in seaweed farmers household is, however, severer than cocoa smallholders. In broad sense, this leads to argue that rural coastal poverty is truly severer than rural agriculture poverty; (2) the orientation of coffee, cashew-nut and livestock productions in agricultural economic activity is strong and directly associated with the poverty of cocoa smallholders. Meanwhile, the orientation of seaweed production in economic activity is strong and directly associated with the poverty of seaweed farmers. These imply that, encouraging coffee, cashew-nut and livestock productions for cocoa smallholders and seaweed production for seaweed farmers by improving access to primary input/seeds in particular (for local government policy), can be strongly expected to reduce poverty directly; (3) there are also common factors responsible for the poverty that requiring general policy options (national government). The options are expanding cultivated land area for cocoa smallholders and stretching length area for seaweed farmers, providing transfer-source income, and stepping up agriculture/aquaculture & nonagriculture extensions (technology, market and input information) can also help poverty reduction efforts.